Éude de la relation entre les fonctions respiratoires et les performances sportives chez des escrimeurs : une étude prospective de cohorte - Kurt, A. G.; Acar, M. (Science & Sports, 2026)
Background Although fencers compete throughout the day while wearing protective masks and clothing that may restrict airflow and chest expansion, the effect of respiratory functions on fencing performance has not been fully clarified in the literature. This study aimed to investigate the associations between respiratory parameters and various components of sports performance in fencers.